Dry Matter Production by Eucalyptus Camaldulensis Dehn Plantation in Jabalpur - Prasad, Ram; Sah, A. K.; Bhandari, A. S.; Chaubey, O. P. (Indian Forester, 1984)
The present investigation was undertaken on 15 year old (1969) and 5 year old (1979) plants of Eucalyptus camoldulensis Dehn raised on the area of Regional Forest Research Centre, Jabalpur. The entire area of planlation was divided in 5 equal compartments. Five trees from each compartment were randomly selected and felled for aboveground and belowground biomass studies. Growlh parameters in 15 year old plantation were 2-4 times that of plants in 5 year old plantations. The root length was traced to a depth of less than 3 m in all cases. However, the lateral spread was unimaginably very vast. The mean lateral spread of 20.3 m was observed in 15 year old plants and 9.01 m in 5 year old plants. The propaganda against Eucalyptus that it is responsible for drying-up of underground water reserVe is thus disproved from these studies. These Vast lateral root system, may be responsible to utilise even the slighest amount of surface moisture which may be available just below the surface in any form of precipitation. In terms of mean annual productivIty it was 15.92 t/h/year in 15 year old plants and 6.03 t/h year in 5 year old plants. The maximum contribution to the total aboveground biomass has been observed by stemwood in both plantations.